(untitled) (Bangladesh Journal of Medical Microbiology, 2026)
Background: The global rise of multidrug-resistant Klebsiella pneumoniae poses a significant challenge to human health. Colistin, a last-resort antibiotic for multidrug-resistant infections, is losing its effectiveness due to extensive use. Objective: The purpose of the study was to detect colistin resistance among clinical isolates of Klebsiella pneumoniae and identify the colistin resistance genes by Polymerase Chain Reaction (PCR). Methodology: This cross-sectional study was conducted in the Department of Microbiology of Dhaka Medical College, Dhaka, Bangladesh from January 2021 to December 2021. Klebsiella pneumoniae was isolated and identified by standard microbiological procedures. The antibiotic susceptibility pattern of all tested antibiotics was determined by the disc-diffusion method. The Minimum Inhibitory Concentration (MIC) of colistin was determined by agar dilution method. PCR was used to identify different colistin resistance genes (phoP, phoQ, mgrB, pmrA, pmrB, pmrC, mcr-1, mcr-2). Results: Out of 55 isolated Klebsiella pneumoniae, 19 (34.55%) were resistant to colistin detected by agar dilution method. MIC of colistin showed a significant rise ranging from 4 to ≥256 μg/ml. A total of 36 (65.45%) K. pneumoniae isolates were found to be multidrug-resistant (MDR). Among 19 colistin resistant isolates, 15 (78.9%) were positive for mgrB and pmrC, 14(73.9%) for pmrB, 13(68.4%) for pmrA, 11(57.9%) for phoP and 10(52.6%) were positive for phoQ. Conclusion: This study showed a high rate of colistin resistance among multidrug-resistant Klebsiella pneumoniae isolates. Strict implementation of antimicrobial stewardship policies are essential to control the spread of colistin resistance. Bangladesh Journal of Medical Microbiology, July 2025;19 (2):89-94